Correction: Highly efficient cuprous complexes with thermally activated delayed fluorescence and simplified solution process OLEDs using the ligand as host. Issue 6 (14th February 2015) - Chen, Xu-Lin; Lin, Chen-Sheng; Wu, Xiao-Yuan; Yu, Rongming; Teng, Teng; Zhang, Qi-Kai; Zhang, Qing; Yang, Wen-Bing; Lu, Can-Zhong
<x xml:space="preserve">Abstract</x> Correction for 'Highly efficient cuprous complexes with thermally activated delayed fluorescence and simplified solution process OLEDs using the ligand as host' by X.-L. Chen et al., J. Mater. Chem. C, 2015, DOI: ; Web: 10.1039/c4tc02255f.